2016
DOI: 10.1080/10773525.2016.1200206
|View full text |Cite
|
Sign up to set email alerts
|

Field comparison of two inhalable samplers used in Italy to measure the wood dust exposure

Abstract: Background: Particle size affects the performance of personal air samplers used to measure dust exposure in the workplace. Few field studies have been conducted for comparing the performance of personal inhalable samplers. Objective: To compare wood dust sampling with two inhalable samplers: IOM (Institute of Occupational Medicine) and Italian cone. Methods: 136 Italian cone/IOM paired samples and 136 passive IOM samples were collected in 30 Italian woodworking industries. The valid number of sample pairs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…The IOM head has been compared with other inhalable samplers, e.g., the Button sampler [ 32 ] and with the CIP 10-l sampler [ 33 ]. Inhalable samplers less commonly compared included the Italian Cone Sampler [ 34 ] which was compared with the IOM sampler and the Gesamtstaub-Probenahmesystem (GSP) sampler [ 35 , 36 ] which was compared with the Button, IOM sampler, 37-mm CFC, and the CIP-10l samplers [ 35 ] as well as the 37-mm CFC sampler [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The IOM head has been compared with other inhalable samplers, e.g., the Button sampler [ 32 ] and with the CIP 10-l sampler [ 33 ]. Inhalable samplers less commonly compared included the Italian Cone Sampler [ 34 ] which was compared with the IOM sampler and the Gesamtstaub-Probenahmesystem (GSP) sampler [ 35 , 36 ] which was compared with the Button, IOM sampler, 37-mm CFC, and the CIP-10l samplers [ 35 ] as well as the 37-mm CFC sampler [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were identified in metals/metalloids workplace settings ( Appendix C ) including for aluminium [ 39 ], lead [ 41 ] and alloys such as copper-beryllium [ 36 ]. Five studies were identified as comparing samplers in wood processing environments [ 32 , 33 , 34 , 35 , 40 ]. Agriculture settings accounted for two studies [ 30 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences could be explained considering different tasks performed by workers in the industries belonging to the wood sector. The different processes are known to produce particles with different size: smaller particles are associated with sanding, while larger particles with planning and shaping processes [ 41 ]. Concerning FA, the lower mean concentrations were found in the furniture industry and in the doors factory, among which no significant differences were found.…”
Section: Discussionmentioning
confidence: 99%